Wearable transparent thermal sensors and heaters based on metal-plated fibers and nanowires. Issue 42 (18th October 2018) - Jo, Hong Seok; Kwon, Hyuk-Jin; Kim, Tae-Gun; Park, Chan-Woo; An, Seongpil; Yarin, Alexander L.; Yoon, Sam S.
Abstract : Electrospun metal-plated nanofibers and supersonically sprayed nanowires were used to fabricate hybrid films exhibiting a superior low sheet resistance of 0.18 Ω sq −1, a transparency of 91.1%, and a figure-of-merit of 2.315 Ω −1 . Abstract : Electrospun metal-plated nanofibers and supersonically sprayed nanowires were used to fabricate hybrid films exhibiting a superior low sheet resistance of 0.18 Ω sq −1, a transparency of 91.1%, and a figure-of-merit of 2.315 Ω −1 . The films are suitable to serve as thermal sensors and heaters. Such hybrid transparent conducting films are highly flexible and thus wearable. They can be used as body-temperature monitors and heaters. The employed hybrid approach improved the sheet resistance diminishing it to a minimum, while maintaining transparency. In addition, the low sheet resistance of the films facilitates their powering with a low-voltage battery and thus, portability. The thermal sensing and heating capabilities were demonstrated for such films with various sheet resistances and degrees of transparency. The temperature sensing was achieved by the resistance change of the film; the resistance value was converted back to temperature. The sensing performance increased with the improvement in the sheet resistance. The temperature coefficient of resistivity was TCR = 0.0783 K −1 . The uniform distribution of the metal-plated nanofibers and nanowires resulted in a uniform Joule heating contributing to an efficient convection heat transfer from the heaters to the surrounding, demonstrated by an improved convective heat transfer coefficient.